Ultra-early indicators of acute hypertriglyceridemic pancreatitis may influence treatment decision-making - Jing Wu; Yizhi Liang; Xiaoting Tang; Zilan Rao; Chaowei Li; Xiaoping Pan; Taiyong Fang (Scientific Reports)
Abstract This study aimed to explore whether ultra-early indicators can predict the severity of acute hypertriglyceridemic pancreatitis (HTGP) and guide clinical decisions. This retrospective study analyzed data from HTGP patients who were categorized into mild acute pancreatitis (MAP) and moderately severe/severe acute pancreatitis (MSAP/SAP) groups based on their final clinical outcomes. Ultra-early indicators (serum calcium, triglyceride [TG], interleukin-6 [IL-6], D-dimer, hemoglobin A1c [HbA1c], arterial lactate) were measured within 6 h of admission. Among 110 patients, 56 had MAP and 54 had MSAP/SAP. Within 6 h of admission, TG, IL-6, D-dimer, HbA1c, and arterial lactate levels were significantly higher in the MSAP/SAP group, while serum calcium was lower. Multivariable logistic regression and receiver operator characteristic curve identified IL-6, D-dimer, and serum calcium as independent risk factors and ultra-early predictors of HTGP severity. Patients with MSAP/SAP who received blood purification within 24 h had a shorter hospital stay compared to those treated later. IL-6, D-dimer, and serum calcium are promising biomarkers for early prediction of HTGP severity. Early blood purification within 24 h reduces complications and hospital stay in MSAP/SAP patients, while traditional treatments remain effective for MAP patients, potentially reducing medical costs.